?Complexes of Zr(IV) and U(VI) with Trans-[14]-diene - ISLAMR, M.SHAMSUL; TARAFDE, M.T.H.; BANU, L.A. (Biological Sciences - PJSIR, 1996)
ethanol (30 cm'). The white product obtained was filtered, washed and stored as above.